Outcomes of Bereavement Care Among Widowed Older Adults With Complicated Grief and Depression - Ghesquiere, Angela (2013)
Bereavement is common among older adults and may result in major depression or complicated grief (CG). Little is known about the effectiveness of physician care for these conditions. We examined whether, among older adults with CG and/or major depression, using physician support was associated with reductions in grief, depression, or anxiety severity. Outcomes were compared to group and religious support. We analyzed data from the Changing Lives of Older Couples (CLOC) Study, a prospective cohort study of married couples in the Detroit area. Spousal death was tracked over 5 years, and follow-up interviews conducted with widowed participants at 6 months (wave 1) and 18 months (wave 2) post loss. Analyses were limited to those with CG or depression with support-seeking data (weighted n = 89). Yes/no items asked whether participants had seen each provider for help with grief up until wave 1. A 19-item grief severity measure was developed by CLOC researchers. The 20-item Center for Epidemiologic Studies Depression scale measured depression severity. The Symptom Checklist 90–Revised assessed anxiety severity. Regressions indicated that seeking support from a family doctor at wave 1 was not associated with changes in anxiety, depression, or grief severity at wave 2 (P > .05). However, support group use was associated with reductions in grief severity (β = −8.46, P < .05), and religious leader support-seeking associated with reductions in depression severity (β = −10.12, P < .01). Findings imply that physician care for grief may not be effective, and support group referral may be helpful. Physicians may benefit from training in recognizing and appropriate referring for bereavement-related distress.